2017
DOI: 10.1097/id.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Ridge Splitting Versus Autogenous Onlay Bone Grafting

Abstract: When reconstructing vertically sufficient but horizontally insufficient alveolar ridges, ridge splitting technique could shorten the treatment period, decrease postoperative swelling and pain, eliminate the need for a second surgical site, reduce the treatment cost, and ease the patient cooperation to the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…The complication rate is low (6.8%), the most common being a buccal bone fracture. Altiparmak et al 7 also reported the buccal bone fracture as the most commonly seen complication, followed by temporary graft exposure. We observed several intraoperative and postoperative complications, all of which were managed uneventfully.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The complication rate is low (6.8%), the most common being a buccal bone fracture. Altiparmak et al 7 also reported the buccal bone fracture as the most commonly seen complication, followed by temporary graft exposure. We observed several intraoperative and postoperative complications, all of which were managed uneventfully.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is important to note that there should be a layer of cancellous bone between the cortical plates to enable splitting. 7 - 9 In a systematic review on ridge augmentation techniques, Milinkovic and Cordaro 15 stated that the mean initial horizontal thickness where autogenous block grafts were used was 3.2 mm (range, 2.5 to 3.89 mm). The linear bone gain was 4.3 mm (range 2.7 to 5.0 mm) after a healing time of approximately 5.6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various techniques were suggested for augmentation of the thin alveolar ridge such as guided bone regeneration (GBR), onlay bone grafting (OBG), alveolar distraction osteogenesis (ADO), and alveolar ridge-split (ARS) techniques. Considering for alveolar bone augmentation, relevant and better results for implant survival and stability were reported in the literature for ridge splitting technique (4)(5)(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%